Factors associated with smoking among high school students in Korea - Rhie, Sandy; Gwak, Hyesun; Park, Myung Hee; Lee, Byungkoo; Lee, Kyung Eun (International Journal of Contemporary Pediatrics, 2017)
Background: Smoking has been a huge economic burden to health care beneficiary and policy makers.However, most smoking-related diseases are preventable by well-planned smoking cessation programs. Therefore, much effort has been made to reduce smoking behaviors, especially among the younger generation. This study examined the association between adolescent smoking and socioeconomic and demographic factors, and the relationship between smoking and sleep disturbance among high school students in Korea. Methods: A cross-sectional survey was performed during 20 September - 21 October 2006, at 9 randomly selected high schools in the local areas of Gyeonggi province in the mid-western part of Korea (5 schools), and the city of Gwangju in the south-western region of Korea (4 schools). Results: A self-report questionnaire was responded by 2404 high school students. Compared with the never smoker, current smoker was independently correlated with older age (OR 1.4; P = 0.0009), male gender (OR 4.6; P <0.0001), part-time job (OR 2.1; P = 0.0024), monthly allowance (>50/month, OR 1.8; P = 0.0018), and casual alcohol use (OR 14.3; P <0.0001). Nonetheless the smoker group slept longer at night (6.5 vs. 6.0 hour, P <0.0001), they took more sleeping pills than the never-smoker (OR 5.1; 95% CI 1.5-17.3). Adjusting other factors, the smoker showed a positive correlation with symptoms of sleep disturbance (adjusted OR 1.5; 95% CI 1.1-2.2). Conclusion: Smoking in high school students was significantly related to age, gender, family size, money allowance, and alcohol. It was also correlated with sleep disturbances causing insomnia, which could further reduce the quality of sleep and harm to health.